The effect of an educational program according to the style of learning by playing on learning some of the complex skills of Futsal football for students - Yousef, Rashad Tariq; Hilaiel, Saleh Chuaied; Alwan, Hikmit Abdul Sittar (International Journal of Psychosocial Rehabilitation, 2020)
The importance of research is cleared in preparing an educational program according to the style of learning by playing to learn some of the complex skills in Futsal football for students in order to acquire those skills and master them with a high degree, the fact that traditional education tends to single repetitions for learning skills, giving little value to educate in how to practice playing, so that, consisting a gap between learning skills and play, as the aim of the study is to identify the effect of the educational program according to the style of learning by playing in learning some of the complex skills in Futsal football for students, the researchers used the experimental method with a two equal groups which are the controlling and experimental groups, while the research sample was chosen by the researchers from the fifth grade preparatory school, at “Muhammad Baqir Al-Sadr” School for Boys, Dhi Qar Governorate in the academic year 2018/2019, the number of the student has reached (30) students, they were divided into control and experimental groups, with (15) students for each group, as the experimental group implemented the educational program according to the style of learning by playing, mean while the control group implemented the teacher’s style, then the researchers concluded that the experimental group that implemented the educational program according to the style of learning by playing have learned some of the complex skills of Futsal football for students.